Analisis Pengaruh Umur Dan Kapasitas Silinder Terhadap Emisi Gas Buang Co2 Pada Sepeda Motor - Sintong Getsemani; Muhammad Reza; Aryo Sasmita (Jurnal Online Mahasiswa (JOM) Bidang Teknik dan Sains, 2020)
BPS data shows that motorbikes are the most widely used vehicle and the number continues to increase every year. This has a negative impact, namely increasing motorcycle exhaust emissions and endangering the environment and human health. The study states that the cylinder capacity and age of the motorcycle have a significant effect on the resulting exhaust emissions. Currently, the most motorbikes on the market are motorcycles with cylinder capacities of 110 cc, 125 cc and 150 cc with a service life of under 5 years. The purpose of this study was to measure CO2 exhaust emissions and to analyze the effect of cylinder capacity and service life on exhaust gases produced using SPSS v. 24.0. This research was conducted by direct measurement using a gas analyzer on a motorcycle in idle condition and the results were analyzed using SPSS v. 24.0. The results showed that the value of CO2 produced in motorcycle samples at various ages and cylinder capacities was below 12%. Keywords: Exhaust Gas Emission, Motorcycle, Idle Condition.